The Davis dynasty : - Rothchild, John (John Wiley & Sons, 2003)
This compelling new narrative from bestselling author John Rothchild tells the story of three generations of the legendary Davis family, who rank among the most successful investors in the history of the Street. With a novelist's wit and eye for telling detail, Rothchild chronicles the financial escapades of this eccentric, pioneering clan, providing a vivid portrait of fifty years of Wall Street history along the way. Rothchild shadows the Davis family's holdings through two lengthy bull markets, two savage and seven mild bear markets, one crash, and twenty-five corrections and, in the process, reveals the strategies behind the family's uncanny ability to consistently beat the markets.